FAKTOR-FAKTOR YANG MEMENGARUHI LOYALITAS PENGGUNA OVO PADA GRAB - Andres Dharma Nurhalim (STIE Wiyatamandala, 2019)
The purpose of the research is to analyze the factors that influence the loyalty of OVO users in Grab. The analytical method used by the author in conducting this research is to use quantitative research as many as 311 respondents who are OVO users in Grab. In conducting data collection, it was done by distributing questionnaires containing several statements. in this study the variables are divided into several parts including Consumer Satisfaction (X1), Price (X2) and Information Quality (X3) as independent variables, and Consumer Loyalty (Y) as the dependent variable. To measure the magnitude of the influence on these variables, the author uses the method of multiple regression analysis. From the results of the analysis it was found that there were significant and simultaneous effects on the variables of customer satisfaction, price and information quality, and consumer loyalty.